Гірські євреї Куби: минуле і сучасність - Таран, О. (Народна творчість та етнографія, 2009)
Using historical and ethnographic materials this paper describes the mountain Jews of Guba – subethnos inhabiting the territory of modern Azerbaijan. We examine certain aspects of their domestic and religious life today. The article used the author’s field research in summer 2008.